High-Performance Organization untuk Menghadapi Turbulensi Lingkungan Bisnis - Andriya Risdwiyanto (Jurnal Maksipreneur, 2017)
Today’s businesses face unprecedented challenges. Leaders are confronted with increased competition, globalization, demand for growing social responsibilities, technological changes, and new strategic thinking. These need to be managed to build and sustain a high-performance organization (AMA, 2007). The organizational environment is anything that is around an organization that has an influence, either directly or indirectly on the process of organization operations. Every organization, either a profit organization and a non-profit organization, such as mass organizations, foundations, and others, want growth and sustainability in every activity. Organizational development does play an important role in helping organizations to transform themselves, through highly planned strategies and with predictions of problems that may be addressed through solutions. The organization will need more ability to react quickly and anticipate the various turbulences it faces appropriately. High-performance organization (HPO) is a solution to face increasingly unpredictable changes.